LEGAL PROTECTION AGAINST ILLEGAL MINING IN THE DEEP SEA IN INDONESIAN - Nawwar, Muhammad Ikhsan (Pusat Unggulan Ipteks-PUI Universitas Jambi, 2025)
This research aims to investigate the methods used by law enforcement to combat maritime illicit mining crimes. The main focus of this journal is on The purpose of this research is to investigate the implementation of the provisions of Law No. 32/2009 relating to the principles of environmental preservation in Indonesia as well as the role of the government in maintaining environmental sustainability in the country. The research methodology used is a normative juridical approach, and it makes use of primary legal materials like the 1945 Constitution, statutory rules, and other legal regulations, coupled with secondary data gathered from sources like academic literature, research papers, and other information. The results show that illegal coal mining activities cause degradation of Indonesia's aquatic ecosystems, This has to do with Law Number 3 of 2020's stipulations. This study highlights how crucial legal analysis is. of illegal coal mining that damages Indonesia's aquatic environment by considering Law No. 3/2020 and other relevant regulations that need to be updated.